2001
DOI: 10.1046/j.0014-2956.2001.02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase has no control on lactate production but has a strong negative control on formate production in Lactococcus lactis

Abstract: A series of mutant strains of Lactococcus lactis were constructed with lactate dehydrogenase (LDH) activities ranging from below 1% to 133% of the wild-type activity level. The mutants with 59% to 133% of lactate dehydrogenase activity had growth rates similar to the wild-type and showed a homolactic pattern of fermentation. Only after lactate dehydrogenase activity was reduced ninefold compared to the wild-type was the growth rate significantly affected, and the ldh mutants started to produce mixed-acid produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 36 publications
0
54
1
Order By: Relevance
“…The inferior characteristics observed for the Ldh enzyme present in this strain are reflected in the observation that the lactateproducing capacity in this strain never exceeded approximately 85% of the total carbon flux, which is significantly lower than that observed in wild-type cells (Ͼ95%) (20,43). Previously, it has been shown that the las operon-encoded Ldh enzyme has a low degree of control over lactate formation rates in L. lactis (1), which is in agreement with the metabolic predictions generated by the kinetic model of the lactococcal pyruvate metabolism (23). However, replacement of the las operon-encoded Ldh enzyme with LdhB in that same model confirms the metabolic values reported here (data not shown; reference 23; jjj .biochem.sun.ac.za/wcfs.html).…”
Section: Discussionmentioning
confidence: 99%
“…The inferior characteristics observed for the Ldh enzyme present in this strain are reflected in the observation that the lactateproducing capacity in this strain never exceeded approximately 85% of the total carbon flux, which is significantly lower than that observed in wild-type cells (Ͼ95%) (20,43). Previously, it has been shown that the las operon-encoded Ldh enzyme has a low degree of control over lactate formation rates in L. lactis (1), which is in agreement with the metabolic predictions generated by the kinetic model of the lactococcal pyruvate metabolism (23). However, replacement of the las operon-encoded Ldh enzyme with LdhB in that same model confirms the metabolic values reported here (data not shown; reference 23; jjj .biochem.sun.ac.za/wcfs.html).…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of glucose, pyruvate, lactate, formate, acetoin, acetate, and ethanol by HPLC was performed as described previously (1).…”
Section: Methodsmentioning
confidence: 99%
“…Andersen and colleagues used modulation of gene expression to show that lactate dehydrogenase has no control on the glycolytic flux in L. lactis MG1363 (1). Phosphofructokinase (PFK), on the other hand, appeared to be present in a very low excess, and even a small reduction of PFK activity resulted in an almost proportional decrease in the glycolytic flux (2).…”
mentioning
confidence: 99%
“…The activities of PYK and LDH have previously been shown to affect pyruvate metabolism in L. lactis (1,7), and differences in fermentation patterns between glucose and maltose could thus be due to differences in the specific activities of these enzymes on maltose. The specific activities of the three las enzymes in wild-type strain MG1363 grown on maltose and on glucose were therefore measured and found to be almost identical (data not shown).…”
mentioning
confidence: 99%
“…One study focusing on the las operon, coding for phosphofructokinase (PFK), pyruvate kinase (PYK), and LDH (9), revealed that LDH has a strong negative effect on the mixed acid flux; the flux control coefficient was less than Ϫ1, meaning that a 10% reduction in LDH leads to a Ͼ10% increase in the mixed acid flux (1). Another study revealed that PYK exhibits strong positive control of formate and acetate production (flux control coefficient for PYK on the formate and acetate flux were both close to 1) (7).…”
mentioning
confidence: 99%